2021
DOI: 10.3389/fnins.2021.678978
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Diffusion Kinetics of Ketamine in Brain Tissue: Implications for in vitro Mechanistic Studies of Drug Actions

Abstract: Ketamine has been in use for over 50 years as a general anesthetic, acting primarily through blockade of N-methyl-D-aspartate receptors in the brain. Recent studies have demonstrated that ketamine also acts as a potent and rapid-acting antidepressant when administered at sub-anesthetic doses. However, the precise mechanism behind this effect remains unclear. We examined the diffusion properties of ketamine in brain tissue to determine their effects in in vitro studies related to the antidepressant action of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…This strongly suggests that our wash-in applications did not reveal the full effect of the applied drug concentrations, presumably because of delayed equilibration between the medium and the slice. This interpretation is strongly supported by studies of diffusion of ketamine and propofol (Gredell et al 2004; Geiger et al 2021). Therefore, our discussion and conclusions are primarily based on our 2 h pre-incubation results.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This strongly suggests that our wash-in applications did not reveal the full effect of the applied drug concentrations, presumably because of delayed equilibration between the medium and the slice. This interpretation is strongly supported by studies of diffusion of ketamine and propofol (Gredell et al 2004; Geiger et al 2021). Therefore, our discussion and conclusions are primarily based on our 2 h pre-incubation results.…”
Section: Discussionmentioning
confidence: 74%
“…These slices were incubated for at least two hours before performing recordings, to allow the drugs to equilibrate in the tissue. It was previously shown that 2 hours incubation is sufficient to reach concentrations close to equilibrium for propofol near the surface of the slices, at depths down to ~50 µm, where all our somatic whole-cell recordings were obtained, and 2 hours far exceeded the time taken to reach equilibrium for ketamine (Gredell et al 2004;Geiger et al 2021). Control cells in these experiments were from slices incubated for the same duration in standard aCSF, to compensate for any potential time-dependent effects of the incubation per se.…”
Section: Mpfc Slice Preparation Maintenance and Perfusion Of Recordin...mentioning
confidence: 83%
See 1 more Smart Citation
“…Both studies suggest that greater FA in the cingulum (Sydnor et al, 2020 ; Vasavada et al, 2016 ), superior longitudinal fasciculus (Sydnor et al, 2020 ) or forceps major (Vasavada et al, 2016 ) present a biomarker for improved clinical outcomes following single dose ketamine. However, clinical (Sydnor et al, 2020 ) and preclinical (Geiger et al, 2021 ) studies have so far either only examined or reported changes in diffusion properties during and immediately following ketamine administration. To the best of our knowledge, this study is the first to investigate changes in WM microstructure following serial ketamine treatment, and to utilize NODDI in this context.…”
Section: Discussionmentioning
confidence: 99%